Research of partial discharge characteristics features in bushings - D. A. Polyakov; N. A. Tereshchenko; K. I. Nikitin (Омский научный вестник)
The paper is devoted to partial discharge measurement and analysis in switchgear bushings. PD bushing structure analysis is described to assess possible defect sources in bushings. An experimental 10 kV bushing sample with the natural defect is obtained from the bushings’ manufacturer. It is tested using the PD measurement technique. Test results showed significant PD intensity at voltages from 12 kV and higher. We have an assumption that a part of registered discharges occurred in the air close to the high voltage electrode sharp edges. To check this assumption we grind them off and repeated the test. The second test does not show considerable PD characteristics change. Therefore, we assume that the bushing sample has an inner defect because the bushing’s surface is not contaminated to generate surficial discharges. The bushing is researched by a destroying method for defect localization. However, inside the bushing, possible defect locations are not found. It might be connected with the fact that the defect could not be found visually at the test time or the defect is located in the gasket between the high voltage electrode and insulator’s body. Besides, there are determined features of phase-resolved partial discharge patterns in switchgear bushings.